2015
DOI: 10.1177/1470320315588233
|View full text |Cite
|
Sign up to set email alerts
|

Association of ACE insertion or deletion polymorphisms with the risk of coronary restenosis after percutaneous coronary intervention: A meta-analysis

Abstract: Objective: Previous case-control studies on the relationship between the angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphisms and coronary restenosis did not reach the same conclusion. In the present study, we aimed to further evaluate the relationship between the ACE gene I/D polymorphisms and coronary restenosis, after percutaneous coronary intervention (PCI). Methods: By searching PubMed, EMBase, the Chinese Biomedical Literature Database and Wanfang database, we selected 16 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
12
1
1
Order By: Relevance
“…This individual susceptibility may be determined by small changes in genes. Previous studies reported that ACE gene I/D polymorphism was associated with different cancer risk [ 33 , 34 ]. I/D polymorphism is an insertion or deletion polymorphism with −287bp in ACE gene.…”
Section: Discussionmentioning
confidence: 99%
“…This individual susceptibility may be determined by small changes in genes. Previous studies reported that ACE gene I/D polymorphism was associated with different cancer risk [ 33 , 34 ]. I/D polymorphism is an insertion or deletion polymorphism with −287bp in ACE gene.…”
Section: Discussionmentioning
confidence: 99%
“…Miao et al . conducted a meta‐analysis to investigate the association between ACE I/D gene polymorphism and risk of coronary restenosis after percutaneous coronary intervention, and found that D allele was associated with coronary restenosis . Yuan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Miao et al conducted a meta-analysis to investigate the association between ACE I/D gene polymorphism and risk of coronary restenosis after percutaneous coronary intervention, and found that D allele was associated with coronary restenosis. 41 Yuan et al performed a meta-analysis to explore the relationship between ACE I/D gene polymorphism and risk of ischemic stroke, and found that the genotype DD of ACE could increase the risk of ischemic stroke. 42 Zintzaras et al performed a meta-analysis to discuss the correlation between ACE I/D gene polymorphism and coronary artery disease, and found that the D allele and DD genotype were related to the onset of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…ACE is involved in the physiology of the vasculature, blood pressure and inflammation (24). It has been demonstrated that the insertion/deletion (I/D) ACE gene polymorphism is associated with coronary restenosis (25), and may also affect blood Positive ISH staining appears as brown staining. Total ACE integrated optical density in the testes of rats subjected to atropine exposure was significantly reduced compared with control rats (Table II; (27).…”
Section: Discussionmentioning
confidence: 99%